Distribution of vortex lattice melting temperatures in mixed state diagram of Bi2212 tapes - Pekala, M; Bougrine, H; Gadomski, W; Morgan, C; Grovenor, C; Cloots, R; Ausloos, M (1998)
The electrical resistivity in the mixed state of Bi2212 tape superconductors can be accurately reconstructed for values below approximately a half of the normal state value of resistivity, assuming a Gaussian distribution for the vortex lattice melting temperatures. The magnetic field dependences of the distribution width and of the dBc2/dT parameter were calculated. Moreover the vortex liquid viscosity coefficient was determined between the vortex lattice melting temperature and Tc at various magnetic fields. It is pointed out that the vortex lattice melting transition should not be confused with the irreversibility line of magnetic studies nor with the percolation temperature line for electrical resistivity. © 1998 Elsevier Science B.V. All rights reserved.